EFFECTIVENESS OF INTERNAL CONTROL SYSTEMS AND GOOD UNIVERSITY GOVERNANCE ON FRAUD PREVENTION WITH ORGANIZATIONAL COMMITMENT - Audra Nailufar; Eka Nurmala Sari; Dahrani Dahrani (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study investigates the influence of the Internal Control System (ICS) and Good University Governance (GUG) on fraud prevention, with organizational commitment serving as a moderating variable. The research was conducted at private universities (PTS) under the supervision of LLDIKTI Region I in Medan City. The study was motivated by the increasing cases of fraud in the higher education sector, particularly the misuse of student aid funds, which threaten institutional integrity, accountability, and sustainability.METHODOLOGY - A quantitative research design was employed, with respondents consisting of university leaders and administrative staff selected through purposive sampling. Data were collected using a structured questionnaire covering ICS, GUG, organizational commitment, and fraud prevention. Instrument validity and reliability were tested to ensure measurement accuracy. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct effects and moderating relationships.FINDING - The findings demonstrate that the effectiveness of ICS has a positive and significant impact on fraud prevention. Likewise, the application of GUG principles contributes significantly to reducing the risk of fraud. Furthermore, organizational commitment strengthens the relationship between ICS, GUG, and fraud prevention, indicating its role as an effective moderating factor. The study concludes that fraud prevention in higher education requires a comprehensive approach that integrates control systems, governance practices, and organizational commitment. These results provide valuable insights for policymakers and higher education leaders in promoting transparency, accountability, and integrity across institutions